Hydrogen sensing via anomalous optical absorption of palladium-based metamaterials. (22nd March 2016) - Hierro-Rodriguez, A; Leite, I T; Rocha-Rodrigues, P; Fernandes, P; Araujo, J P; Jorge, P A S; Santos, J L; Teixeira, J M; Guerreiro, A
Abstract: A palladium (Pd)-based optical metamaterial has been designed, fabricated and characterized for its application in hydrogen sensing. The metamaterial can replace Pd thin films in optical transmission schemes for sensing with performances far superior to those of conventional sensors. This artificial material consists of a palladium–alumina metamaterial fabricated using inexpensive and industrial-friendly bottom-up techniques. During the exposure to hydrogen, the system exhibits anomalous optical absorption when compared to the well-known response of Pd thin films, this phenomenon being the key factor for the sensor sensitivity. The exposure to hydrogen produces a large variation in the light transmission through the metamembrane (more than 30% with 4% in volume hydrogen–nitrogen gas mixture at room temperature and atmospheric pressure), thus avoiding the need for sophisticated optical detection systems. An optical homogenization model is proposed to explain the metamaterial response. These results contribute to the development of reliable and low-cost hydrogen sensors with potential applications in the hydrogen economy and industrial processes to name a few, and also open the door to optically study the hydrogen diffusion processes in Pd nanostructures.